Forensic radiocarbon dating of human remains: the past, the present, and the future - Brock, Fiona; Cook, G. T. (Equinox Publishing, 2017)
Radiocarbon dating is a valuable tool for the forensic examination of human remains in answering questions as to whether the remains are of forensic or medico-legal interest or archaeological in date. The technique is also potentially capable of providing the year of birth and/or death of an individual. Atmospheric radiocarbon levels are currently enhanced relative to the natural level due to the release of large quantities of radiocarbon (14C) during the atmospheric nuclear weapons testing of the 1950s and 1960s. This spike, or “bomb-pulse,” can, in some instances, provide precision dates to within 1–2 calendar years. However, atmospheric 14C activity has been declining since the end of atmospheric weapons testing in 1963 and is likely to drop below the natural level by the mid-twenty-first century, with implications for the application of radiocarbon dating to forensic specimens.